Growth hormone deficiency in treated acromegaly and active Cushing's syndrome. Issue 1 (February 2017) - Formenti, Anna Maria; Maffezzoni, Filippo; Doga, Mauro; Mazziotti, Gherardo; Giustina, Andrea
Abstract : Growth hormone deficiency (GHD) in adults is characterized by reduced quality of life and physical fitness, skeletal fragility, increased weight and cardiovascular risk. It may be found in (over-) treated acromegaly as well as in active Cushing's syndrome. Hypopituitarism may develop in patients after definitive treatment of acromegaly, although the exact prevalence of GHD in this population is still uncertain because of limited awareness, and scarce and conflicting data so far available. Because GHD associated with acromegaly and Cushing's syndrome may yield adverse consequences on similar target systems, the final outcomes of some complications of both acromegaly and Cushing's syndrome may be further affected by the occurrence of GHD. It is still largely unknown, however, whether GHD in patients with post-acromegaly or active Cushing's syndrome (e.g. pharmacologic glucocorticoid treatment) may benefit from GH replacement. We review the diagnostic, clinical and therapeutic aspects of GHD in adults treated for acromegaly and in those with active Cushing's syndrome.